A study on fatty liver in patients admitted to medical wards in tertiary hospital - Shaik, Khwaja Ubedullah; Deepthi, K. Gnana; Nagabhushana, M. V.; Keerthana, B. (International Journal of Advances in Medicine, 2018)
Background: Fatty liver is a common clinical condition seen in medical wards. It can be either alcoholic fatty liver disease or non-alcoholic fatty liver disease. It is an iceberg phenomenon which can be associated with metabolic syndrome, cardiovascular disease and hepatocellular carcinoma. The aim of the present study is to observe and analyse the prevalence of fatty liver diseases in general population admitted to general wards in department of general medicine and to help in the timely prevention of associated risk factors and complications Methods: It is a prospective cross-sectional study conducted in Narayana medical college and hospital a tertiary care hospital for a period of 6 months from November 2017 to May 2018 and includes a total of 250 patients. Patients were routinely screened with ultrasound abdomen and those having fatty liver changes were included in this study and their clinical and biochemical parameters were examined. Results: Out of the 250 patients admitted to medical wards during the study period, 70 patients (28%) had fatty liver. Out of these, 23 (34%) were males and 47 (67%) were females, alcoholics were 9 (12.8%) and non-alcoholics were (87.2%), 35 (50%) were diabetics, 11 (15.7%) had CAD (coronary artery disease), 29 (41.4%) were obese with BMI >30 and 26 (37.1%) were hypertensive. Conclusions: Fatty liver is a common incidental finding in ultrasound abdomen in patients admitted to medical wards and when neglected, which when given importance and with proper intervention and life style modifications can prevent metabolic syndrome, cardiovascular disease and hepatocellular carcinoma.